To love and to cherish [large type] - Irvin, Kelly (Irvin, Kelly. Bliss Creek Amish, 2012)
It's been four years since Carl left. Four years since he left the safety of the small Amish community for the Englisch world. And in four years, Emma's heart has only begun to heal. Now, with the unexpected death of her parents, Emma is plunged back into a world of despair and confusion. It's a confusion only compounded by Carl's return. She's supposed to be in love with him...so why can't she keep her mind off Thomas, the strong, quiet widower who always seems to be underfoot? Could the man she only knew as a friend be the one to help her to heal? In a world that seems to be changing no matter how tightly she clings to the past, this one woman must see beyond her pain and open her heart to trust once again.